Silo: Predictable Message Latency in the Cloud - Jang, Keon; Sherry, Justine; Ballani, Hitesh; Moncaster, Toby (SIGCOMM, 2015)
Many cloud applications can benefit from guaranteed latency for their network messages, however providing such predictability is hard, especially in multi-tenant datacenters. We identify three key requirements for such predictability: guaranteed network bandwidth, guaranteed packet delay and guaranteed burst allowance. We present Silo, a system that offers these guarantees in multi-tenant datacenters. Silo leverages the tight coupling between bandwidth and delay: controlling tenant bandwidth leads to deterministic bounds on network queuing delay. Silo builds upon network calculus to place tenant VMs with competing requirements such that they can coexist. A novel hypervisor-based policing mechanism achieves packet pacing at sub-microsecond granularity, ensuring tenants do not exceed their allowances. We have implemented a Silo prototype comprising a VM placement manager and a Windows filter driver. Silo does not require any changes to applications, guest OSes or network switches. We show that Silo can ensure predictable message latency for cloud applications while imposing low overhead.